The appearance of place identity in the urban landscape by using the natural factors (a case study of Yasouj) - Moshaver, Mehrdad Karimi; Negintaji, Farshad; Zeraatpisheh, Hamid Reza (Journal of Architecture and Urbanism, 2015)
This study has examined the effects of natural factors (urban landscape) on the place identity. In order to perform this, the place identity has been measured and also its relationship with the components of natural factors, absolute elements, living elements and natural elements have been measured. The study is descriptive and the statistical population has been Yasouj which is a city in Iran. To analyze the data the SPSS software has been used. The results have been investigated in two levels of descriptive and inferential statistics. In the inferential statistics, Pearson correlation coefficient has been used to evaluate the research hypotheses. In this study, the variable of place identity is in high level and the natural factors are also in high level which these results indicate a positive relationship between place identity and natural factors. The results indicate that natural factors have significant role on Yasouj landscape and also increase the place identity. It can be inferred that the development of natural factors and reaching it to the qualified level will develop the place identity.